2020
DOI: 10.15252/embj.2019103838
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide depletion reveals the impaired ribosome biogenesis checkpoint as a barrier against DNA damage

Abstract: Many oncogenes enhance nucleotide usage to increase ribosome content, DNA replication, and cell proliferation, but in parallel trigger p53 activation. Both the impaired ribosome biogenesis checkpoint (IRBC) and the DNA damage response (DDR) have been implicated in p53 activation following nucleotide depletion. However, it is difficult to reconcile the two checkpoints operating together, as the IRBC induces p21‐mediated G1 arrest, whereas the DDR requires that cells enter S phase. Gradual inhibition of inosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 63 publications
(113 reference statements)
1
19
0
Order By: Relevance
“…In both cases, by exploiting a vestigial function (which in wtp53 is designed for execution in late S-G2 phase to preserve genome integrity as cells advance towards mitosis) mtp53 uses these activities at S-phase entry to expedite chromosomal replication, presumably at the expense of the quality control mechanisms that coordinate the spatio-temporal regulation of replication with DNA repair pathways [59]. Consistent with this idea, it is interesting that we observed the parental MDA-MB-468 R273H cells progress through S-phase fastest when synchronized with RNR inhibitors, which produce a type of damage repaired by excision repair pathways such as BER, NER, and MMR that are active within G1 (BER, NER) and throughout S-phase (BER and MMR) respectively [58,66]. Moreover, the slower progression through S-phase demonstrated by the R273HΔ347-393 and R273HΔ381-388 CRISPR cell lines in response to thymidine may suggest a role for the C-terminus of mtp53 in repair and/or bypass of damage monitored by such repair pathways, leaving damage to be dealt with in late S/G2 phase.…”
Section: Figure 6: Defective Dna Replication Underscores the Thymidine Sensitivity Of Mda-mb-468 Crispr-cas9 Generated Mtp53-depleted Celsupporting
confidence: 59%
See 2 more Smart Citations
“…In both cases, by exploiting a vestigial function (which in wtp53 is designed for execution in late S-G2 phase to preserve genome integrity as cells advance towards mitosis) mtp53 uses these activities at S-phase entry to expedite chromosomal replication, presumably at the expense of the quality control mechanisms that coordinate the spatio-temporal regulation of replication with DNA repair pathways [59]. Consistent with this idea, it is interesting that we observed the parental MDA-MB-468 R273H cells progress through S-phase fastest when synchronized with RNR inhibitors, which produce a type of damage repaired by excision repair pathways such as BER, NER, and MMR that are active within G1 (BER, NER) and throughout S-phase (BER and MMR) respectively [58,66]. Moreover, the slower progression through S-phase demonstrated by the R273HΔ347-393 and R273HΔ381-388 CRISPR cell lines in response to thymidine may suggest a role for the C-terminus of mtp53 in repair and/or bypass of damage monitored by such repair pathways, leaving damage to be dealt with in late S/G2 phase.…”
Section: Figure 6: Defective Dna Replication Underscores the Thymidine Sensitivity Of Mda-mb-468 Crispr-cas9 Generated Mtp53-depleted Celsupporting
confidence: 59%
“…Recently, a metabolite of pyrimidine nucleotide pool imbalance, the dihydropyrimidines (both uracil and thymidine), have been shown to cause DNAprotein crosslinks that can cause both DNA replication and transcriptional stress if left unrepaired [68]. Interestingly, cells enter S-phase with such damage despite robust wtp53 and Chk1 activation, cellular responses shared by cells in which the Impaired Ribosome Biogenesis Checkpoint (IRBC) has been activated by transcriptional stress induced by inhibitors of purine or pyrimidine biosynthesis [66]. Activation of the IRBC was found to halt S-phase entry through wtp53 activation of the cyclin dependent kinase inhibitor p21 [66].…”
Section: Figure 6: Defective Dna Replication Underscores the Thymidine Sensitivity Of Mda-mb-468 Crispr-cas9 Generated Mtp53-depleted Celmentioning
confidence: 99%
See 1 more Smart Citation
“…This response leads to forming DNA:RNA hybrids or R-loops and breakage of DNA double-strand (Pelletier et al, 2018). Thus, the ATM/NBS1/Treacle response is maintained at an appropriate level with the impaired ribosome synthesis checkpoint-p21 response to protect against DNA damage, which suggests that ribosome biogenesis in replicative stress is important (Pelletier et al, 2020). In addition, it has been found that ROS, one of the representatives DDR agents, not only attacks ribosome components but also affects ribosomes indirectly by altering the activities of ribosome-modifying enzymes.…”
Section: Ribophagymentioning
confidence: 99%
“…Their research shows that when purine levels drop, ribosome assembly is delayed, as nucleotides are needed for RNA. This causes failure of cell cycle checkpoint and p21 accumulation, arresting cells in G1 phase (Pelletier et al, 2020). Overexpression of S. cerevisiae p21 analog CIP1 also causes arrest in G1 phase.…”
Section: Discussionmentioning
confidence: 99%